Populismo y neopopulismo: la experiencia peruana - Crabtree, John (1997)
The article examines the populist tradition in Peru's political development over the last fifty years, seeking to draw attention to some of the continuities in the political practice of successive regimes, albeit ones of different ideological orientations. In so doing, it seeks to define 'populism' as a style of government which links the rulers with the ruled bypassing representative systems of political mediation. Whilst typically populism emerges at moment of economic and political crisis, when representative institutions fail lo provide solutions lo popular demands, it also reflects the longstanding weakness of such institutions in Peru this century. Despite the very different orientation of their economic policies, the political methods of the Garcia and Fujimori governments have more in common than is often believed. These continuities reflect, in part, the chasm dividing the state and the rest of society.